Effectiveness of modern methods of controlling myopia progression: a review - Padurska, Maria; Wojtczak-Kwaśniewska, Monika; Przekoracka-Krawczyk, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2025)
The myopia epidemic is becoming a more serious problem every year, increasingly affecting children and adolescents. Consequently, it is predicted that a significant percentage of the adult population will be myopic within the coming years. Current animal and human studies show that the development of myopia is the result of the interaction of genetic factors (it has been observed that the prevalence of myopia is higher in people with one or both myopic parents) and environmental factors (studies suggest that the development of myopia is related to more time spent on near-work activities). This article presents methods to control myopia progression based on relevant research from recent years. The article will discuss the following methods of controlling myopia progression: soft contact lenses, orthokeratology, low-dose atropin, bifocal and multifocal spectacle lenses, and spectacle lenses with DIMS and HAL technology. The article will also discuss studies combining the use of atropine with optical methods.